Histomorphometric Analysis of Adrenal Cortex and Serum Cortisol in Chronic Stress Models - Waqas Iqbal, Hamna Ansari, Ahmad Farzad Qureshi, Sardar Ahmad, Nargis Haider, Zubda Akhtar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Chronic stress disrupts hypothalamic–pituitary–adrenal (HPA) axis homeostasis, producingstructural and functional alterations in the adrenal cortex that may underlie maladaptive glucocorticoid secretion